BEHAVIORAL PROFILE OF PREGNANT WOMEN ATTENDED IN A TESTING AND COUNSELING CENTER IN A FRONTIER MUNICIPALITY - Ana Jessily Camargo Barbosa; Fabiana Bertin; Rosane Meire Munhak da Silva; Jossiana Wilke Faller; Reinaldo Antônio da Silva-Sobrinho; Adriana Zilly (Universidade Federal do Paraná, 2016)
The aim was to identify the behavioral and epidemiological profile of pregnant women attended in Testing and Counseling Centers in a frontier municipality, between 2007 and 2013, and to describe the occurrence of sexually transmitted diseases. It is a descriptive, documentary and retrospective study with 905 women. Attendance at the testing service was related to the prenatal consultation. The pregnant women were young (20 to 29 years old), married or in a stable relationship, Caucasian, and with up to 11 years' education. It was ascertained that 1.66% were positive for Human Immunodeficiency Virus, 0.44% for syphilis, 0.22% for hepatitis B, and 0.22% for hepatitis C. The pregnant women presented behaviors of risk related to non-use of condoms with their steady partner and through the use of licit and illicit drugs. Furthermore, 12.6% reported not using condoms through lack of information. It is concluded that it is fundamental to strengthen actions in the context of the existing public health policies relating to women's different health needs, so as to reduce behaviors of risk.